Foliar CO2 in a holm oak forest subjected to 15 years of climate change simulation - Ogaya, Romà; Llusia, Joan; Barbeta, Adrià; Asensio, Dolores; Liu, Daijun; Alessio, Giorgio Arturo; Penuelas, Josep (Plant Science, 2014)
A long-term experimental drought to simulate future expected climatic conditions for Mediterranean forests, a 15% decrease in soil moisture for the following decades, was conducted in a holm oak forest since 1999. Net photosynthetic rate, stomatal conductance and leaf water potential were measured from 1999 to 2013 in Quercus ilex and Phillyrea latifolia, two co-dominant species of this forest. These measurements were performed in four plots, two of them received the drought treatment and the two other plots were control plots. The three studied variables decreased with increases in VPD and decreases in soil moisture in both species, but the decrease of leaf water potential during summer drought was larger in P. latifolia, whereas Q. ilex reached higher net photosynthetic rates and stomatal conductance values during rainy periods than P. latifolia. The drought treatment decreased ca. 8% the net photosynthetic rates during the overall studied period in both Q. ilex and P. latifolia, whereas there were just non-significant trends toward a decrease in leaf water potential and stomatal conductance induced by drought treatment. Future drier climate may lead to a decrease in the carbon balance of Mediterranean species, and some shrub species well resistant to drought could gain competitive advantage relative to Q. ilex, currently the dominant species of this forest.
Keywords: climate change; Drought; mediterranean forest; phillyrea latifolia; photosynthetic rates; Quercus ilex

Dampening effects of long-term experimental drought on growth and mortality rates of a Holm oak forest - Barbeta, Adrià; Ogaya, Romà; Penuelas, Josep (GLOBAL CHANGE BIOLOGY, 2013)
Forests respond to increasing intensities and frequencies of drought by reducing growth and with higher tree mortality rates. Little is known, however, about the long-term consequences of generally drier conditions and more frequent extreme droughts. A Holm oak forest was exposed to experimental rainfall manipulation for 13years to study the effect of increasing drought on growth and mortality of the dominant species Quercus ilex, Phillyrea latifolia, and Arbutus unedo. The drought treatment reduced stem growth of A. unedo (-66.5%) and Q. ilex (-17.5%), whereas P. latifolia remained unaffected. Higher stem mortality rates were noticeable in Q. ilex (+42.3%), but not in the other two species. Stem growth was a function of the drought index of early spring in the three species. Stem mortality rates depended on the drought index of winter and spring for Q. ilex and in spring and summer for P. latifolia, but showed no relation to climate in A. unedo. Following a long and intense drought (2005-2006), stem growth of Q. ilex and P. latifolia increased, whereas it decreased in A. unedo. Q. ilex also enhanced its survival after this period. Furthermore, the effect of drought treatment on stem growth in Q. ilex and A. unedo was attenuated as the study progressed. These results highlight the different vulnerabilities of Mediterranean species to more frequent and intense droughts, which may lead to partial species substitution and changes in forest structure and thus in carbon uptake. The response to drought, however, changed over time. Decreased intra- and interspecific competition after extreme events with high mortality, together with probable morphological and physiological acclimation to drought during the study period, may, at least in the short term, buffer forests against drier conditions. The long-term effects of drought consequently deserve more attention, because the ecosystemic responses are unlikely to be stable over time.Nontechnical summaryIn this study, we evaluate the effect of long-term (13years) experimental drought on growth and mortality rates of three forest Mediterranean species, and their response to the different intensities and durations of natural drought. We provide evidence for species-specific responses to drought, what may eventually lead to a partial community shift favoring the more drought-resistant species. However, we also report a dampening of the treatment effect on the two drought-sensitive species, which may indicate a potential adaptation to drier conditions at the ecosystem or population level. These results are thus relevant to account for the stabilizing processes that would alter the initial response of ecosystem to drought through changes in plant physiology, morphology, and demography compensation.
Keywords: acclimation; Arbutus unedo; experimental drought; global-change-type drought; Holm oak; mediterranean forest; phillyrea latifolia; Quercus ilex; tree growth; tree mortality; vegetation stabilizing processes

Comparative study of diurnal and nocturnal sap flow of Quercus ilex and Phillyrea latifolia in a Mediterranean holm oak forest in Prades (Catalonia, NE Spain) - Barbeta, Adrià; Ogaya, Romà; Penuelas, Josep (Trees, 2012)
Droughts are a cyclical disturbance in Mediterranean ecosystems and climate change models forecast an increase of their frequency and severity. Some experimental and observational studies have shown that cooccurring species may cope with drier conditions with different strategies and present different responses. Here, we investigate sap ﬂow response to drought in order to explain the observed differential growth and mortality of Quercus ilex and Phillyrea latifolia at Prades Holm oak forest (NE Spain). We measured sap ﬂow of these species and compared their diurnal, nocturnal and seasonal patterns and their relationship with environmental variables. Both species described qualitatively similar daily patterns, either during daylight or night. Sap ﬂow rates were signiﬁcantly higher in P. latifolia except in autumn and spring. P. latifolia was more sensitive to soil moisture. Nocturnal sap ﬂow was detected in both species with no signiﬁcant differences and hourly rates suffered a progressive increase from 3 a.m. to dawn in most sampled nights. Our results indicate a better adaptation of P. latifolia to this site as it can take better advantage of wet periods while maintaining higher sap ﬂow rates during dry periods. Along with previous ecophysiological studies at the same location it may be inferred that at its drier distributional limit Q. ilex would be at disadvantage with respect to other species like P. latifolia, as the latter would cope better with increasing xeric conditions already occurring and further predicted for Mediterranean ecosystems. Our results also show nocturnal sap ﬂow to be relevant in individual water losses in these two species as they can be up to 35–40 % of daily sap ﬂow. Further research on the underlying mechanisms of this nocturnal sap ﬂow is required since it may also enhance early morning CO2 ﬁxation or nutrient supply to leaves.
Keywords: á; Drought; ilex á sap flow; nocturnal sap flow; nocturnal sap flow á; phillyrea latifolia; phillyrea latifolia á quercus; Quercus ilex; sap flow